Textos y géneros en el currículo de portugués de la escuela estadual paulista - Zanchetta Junior, Juvenal [UNESP] (FapUNIFESP (SciELO), 2015)
The article covers the assigned texts included in the educational textbooks for the discipline of Portuguese language in the project São Paulo Faz Escola – SPFE – which began in 2008 and was adopted as a curricular proposal by the Secretaria de Estado da Educação de São Paulo – SEE-SP. The use of verbal and non verbal texts is compared in the São Paulo proposal and in the series Português: linguagens, of William Roberto Cereja and Thereza Cochar Magalhães (Editora Saraiva), an educational collection adapted to the Programa Nacional do Livro Didático – PNLD. The main tool for analysis is the concept of textual genre, according to the definition supported by the Parâmetros Curriculares Nacionais and by the SEE-SP. Among the general findings, the shift away from the notion of genre by the SPFE can be emphasized by the recurring use of texts devoid of social history and the standardization of content present in the above mentioned texts books.
Textos e gêneros no currículo de Português da escola estadual paulista
Texts and genres in the Portuguese curriculum in São Paulo state schools
Keywords: Text books; Text genres; Texts